(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Steganography is the science and art of hiding a secret message in a cover media, without any imperceptible changing in the it. Steganography can be applied in several media such as image, audio, video. This project suggested video steganography method for preserving the confidentiality which is the important requirement in the security field. Two domains namely spatial and frequency domains can be used in the video steganography for embedding the secret message. In this method, a spatial domain basing on the Least Significant Bit (LSB) is used for embedding the secret message. In order to satisfying the security requirement, the philosophy of cryptography is used in the suggested method. In this method the XOR operator is used with embedding operation. XOR is used with three keys in order to increase the security layer. In addition, according to the experimental results, the suggested method satisfied the imperceptibility requirement which is very important requirement in the image steganography field. The experiment results show that the value of all PSNR values (after embedding the secret message in more than cover image) are more than 50dB which mean that the suggested method reduced the distortion that may be occur in the cover after embedding the secret message.